2023
DOI: 10.1111/1750-3841.16427
|View full text |Cite
|
Sign up to set email alerts
|

Differences in habitual eating speed lead to small differences in dynamic sensory perception of composite foods

Abstract: Previous studies demonstrated that variability in oral processing behaviors impacts bolus properties and consequently texture and flavor perception. However, most studies followed a prescribed mastication protocol during the products' sensory evaluations. A better understanding of how variability in habitual eating behavior impacts sensory perception of foods is needed. The aim of this study was to investigate the effect of habitual eating speed (slow vs. fast eaters) on dynamic sensory perception of composite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…Specifically, the carrier–mayonnaise combinations exhibited a faster T max compared to mayonnaises consumed alone . In our study, the changes in aroma release of the jam with bread or sponge cake combinations were too subtle to produce clear changes in aroma intensity perception, which is consistent with earlier findings where differences in eating speed led to only small differences in dynamic sensory perception. ,, …”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Specifically, the carrier–mayonnaise combinations exhibited a faster T max compared to mayonnaises consumed alone . In our study, the changes in aroma release of the jam with bread or sponge cake combinations were too subtle to produce clear changes in aroma intensity perception, which is consistent with earlier findings where differences in eating speed led to only small differences in dynamic sensory perception. ,, …”
Section: Discussionsupporting
confidence: 91%
“…17 In our study, the changes in aroma release of the jam with bread or sponge cake combinations were too subtle to produce clear changes in aroma intensity perception, which is consistent with earlier findings where differences in eating speed led to only small differences in dynamic sensory perception. 12,19,26 Secondly, it was hypothesized that adding solid carriers to strawberry jams leads to an increase in aroma release and a decrease in aroma perception. When jams were combined with bread, the aroma release increased.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies evaluated how differences in consumer characteristics can influence sensory perception. Using TDS, differences in habitual eating speed between consumers led to limited effects on dynamic sensory perception and discrimination ability of composite foods (Gonzalez‐Estanol et al., 2023). It has been reported that analytic–holistic cognitive style differences of consumers can significantly impact perceptions, opinions, and behaviors toward foods.…”
mentioning
confidence: 99%